Urban design and democracy; A proposed comprehensive conceptual framework for assessing democratic public spaces - Navid Asadi; Sina Razzaghi Asl (Journal of Regional and City Planning, 2022)
Cities and public spaces should be regarded as the most valuable achievements of mankind in recent centuries. Nowadays, in some cases, we see a decline in quality of the public sphere, which diminishes the liberty and the voluntary presence of people, who feel no desire to visit certain public spaces. In this paper, we critically review existing knowledge and attitudes applied within the broadly defined field of democratic public spaces and develop a new, more comprehensive framework that better reflects contemporary social challenges in the city of Tehran, Iran. We systemized and unified a broad range of urban democracy-based concepts in an integrated model, i.e., the right to the city, social justice, civil society and citizen’s rights, inclusive design and cities friendly for women, children, the elderly, the disabled, tourists, and minority groups within the city. Data collection was conducted based on the crowdsourcing method through analysis of social networking applications, i.e., Twitter, Instagram, and Foursquare as well as in-depth and semi-structured interviews with experts and the public. As a result, we systematically distinguish five key terms for assessing democratic public spaces, i.e., socio-spatial diversity, social justice, social inclusion, comfort, and public participation. This conceptual framework can be used as a guideline for policy makers and urban designers to create and evaluate public spaces to achieve the most democratic spaces. Our framework was applied to Tehran’s 30Tir street.